How do moral hazard behaviors lead to the waste of medical insurance funds? An empirical study from China - Qin, Yinghua; Liu, Jingjing; Li, Jiacheng; Wang, Rizhen; Guo, Pengfei; Liu, Huan; Kang, Zheng; Wu, Qunhong (Frontiers in Public Health, 2022)
Background: This study aims to explore the relationship between the different actors in the moral hazard activities of the medical insurance fund and the path combination of causes that cause different degrees of fund loss. Methods: Data were derived from 314 typical cases of medical insurance moral hazard reported in Chinese government official websites. Social network analysis (SNA) was utilized to visualize the network structure of the moral hazard activities, and crisp-set qualitative comparative analysis (cs/QCA) was conducted to identify conditional configurations leading to funding loss in cases. Results: Nearly 50% of the immoral behaviors mainly occur in medical service institutions. Designated private hospitals (out-DD=33, CC=0.851) and primary medical institutions (out-DD=30, CC=0.857) are the main actors of medical insurance fraud (in-DD=50, EC=1) associated with false hospitalization, overtreatment, forged medical records, and non-medical insurance items swap medical insurance items. Illegal medical charges (in-DC=26, EC=0.95) are mainly generated in designated public hospitals (out-DD=27, CC=0.865) through repeatedly charged medical expenses, over-standard charges, and privately set up charging items. Besides, designated pharmacies, insured persons, employers, and medical insurance agencies also have immoral behaviors, which corresponding nodes of settling of daily necessities by medical insurance cards, using the borrowed medical insurance cards, forged invoices, and repeated reimbursement need to be monitored. Opportunism without regulatory technology and risky adventurism with economic pressure are two types causing high loss of medical insurance funds, which are related to financial pressure, the non-implementation of regulatory policies, the low level of regulatory technology, the organization's manipulation ability, as well as the local incident rate. Conclusion: There are various types of moral hazard activities in medical insurance, which constitute a complex network of behaviors. Medical insurance moral hazard is related to financial pressure, opportunities, capabilities, and behavioral rationalization. Most of moral hazard activities happen in the medical institutions. The high loss mainly occurs before the government implemented intervention. It’s necessary to strengthen the supervision of medical insurance funds, pay attention to areas with low economic development and high incident rates, as well as focus on monitoring the behaviors of major medical services providers.